STUDI EKTOPARASIT PADA TIKUS DI PELABUHAN KUALA TUNGKAL TAHUN 2019 - Husna, Nadya; Chandra, Emilia (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2020)
Ectoparasites are parasites that live on rats as their hosts, and the port is one of the breeding grounds for rats that must be protected or a place that must be free from rats. Rats can contain ectoparasites that are harmful to human health. This study aims to see the description of ectoparasites in rats at Kuala Tungkal Port, Jambi Province.This study is an exploratory study, which describes ectoparasites in rats in the Kuala Tungkal Port Health Office with an area of 280,000 m2. The research was carried out by installing traps at points that represent the presence of rats.The results found 3 types of mice, namely Mus musculus, Rattus diardii, and Rattus norvegicus, the most types of mice found were Mus musculus. Xenopshylla cheopis ectoparasite was found in Rattus diardii rats. It is necessary to monitor and control rat eradication in the port working area, as well as improve sanitation.Â